Komunikasi Interpersonal Rehabilitasi Pecandu Narkoba di Malang - Ayu Fatihatur Rahmah (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2020)
This article discusses how the interpersonal communication that is built between counselors and drug addicts patients in receiving institutions is obliged to report bahrul maghfiroh cinta indonesia (IPWL BMCI) Malang. This research uses descriptive qualitative research methods. The purpose of this study was to determine the interpersonal communication process carried out between counselors and drug addict patients in IPWL BMCI Malang. The results showed that the interpersonal communication that was built between the counselor and the drug addict patient was: (1) taking a personal approach to the drug addict patient (2) verbal and non verbal communication between the counselor and the drug addict patient (3) making the patient familiar with the counselor (4) ) fostering trust in patients with drug addicts (5) strengthening the kinship system.